MEKANISME PENYELESAIAN KONFLIK LAHAN PADA MASYARAKAT KAWASAN TAMBANG EMAS PT. MASMINDO DWI AREA DI KECAMATAN LATIMOJONG KABUPATEN LUWU - Yusri; Sakaria; Tautoto Tana Ranggina (Journal Publicuho, 2024)
The complexation of the conflict that occurred in the community of the gold mining area of PT. Masmindo Dwi Area in Latimojong forced the parties involved to find a way out of the tension that occurred. This study aims to identify the best practices of land conflict resolution involving several stakeholders in Latimojong. Using a qualitative approach, data was collected through field observations, in-depth interviews and document studies. The results of the study indicate that conflict resolution in the community of the gold mining area of PT. Masmindo Dwi Area in Latimojong was carried out through informal mechanisms (negotiation and mediation) and formal (litigation). Both mechanisms are fairly effective, although in some cases the land conflicts that occurred reached a dead end. This study suggests the need for the use of other, more appropriate approaches to resolve the tensions that occurred. Policies based on local community participation and appropriate compensation for land are the main recommendations for resolving land conflicts at the mine location.